Somatic burden in Russia during the COVID-19 pandemic - Zolotareva, Alena; Khegay, Anna; Voevodina, Elena; Kritsky, Igor; Ibragimov, Roman; Nizovskih, Nina; Konstantinov, Vsevolod; Malenova, Arina; Belasheva, Irina; Khodyreva, Natalia; Preobrazhensky, Vladimir; Azanova, Kristina; et al. (PLoS ONE)
Somatic burden has become one of the most common psychological reactions to the COVID-19 pandemic worldwide. This study examined the prevalence of somatic burden, latent profiles, and associated factors of somatic symptoms during the pandemic in a large sample of Russians. We used cross-sectional data from 10,205 Russians collected during October-December, 2021. Prevalence of somatic burden was assessed with the Somatic Symptom Scale-8. Latent profiles of somatic burden were identified using latent profile analysis. Multinomial logistic regression was used to examine demographic, socioeconomic, and psychological associated factors of somatic burden. Over one-third (37%) of the Russians reported being somatised. We selected the three-latent profile solution with high somatic burden profile (16%), medium somatic burden profile (37%), and low somatic burden profile (47%). The associated factors of greater somatic burden were female gender, lower education, history of COVID-19 disease, refusing vaccination against SARS-CoV-2 infection, poorer self-rated health, greater fear of COVID-19 pandemic, and living in regions with higher excess mortality. Overall, this study contributes to knowledge about the prevalence, latent profiles, and associated factors of somatic burden during the COVID-19 pandemic. It can be useful to researchers in psychosomatic medicine and practitioners in the health care system.